Inhibition of miR-383 suppresses oxidative stress and improves endothelial function by increasing sirtuin 1 - Hu,Baoxiang (2020)
Previous research has shown that suppression of miR-383 can prevent inflammation of the endothelium, as well as postpone the development of atherosclerosis. However, the role of miR-383 in endothelial cell apoptosis in diabetes remains unclear. The aim of this study was to investigate the function of miR-383 in high glucose-induced apoptosis and oxidative stress in endothelial cells. A series of experiments involving qualitative polymerase chain reaction, cell transfection, luciferase assay, assessment of cell death, detection of catalase and superoxide dismutase concentrations, detection of intracellular reactive oxygen species (ROS), and western blot analysis were performed in this study. We found that miR-383 expression was promoted, while NAD+-dependent deacetylase and sirtuin 1 (SIRT1) expressions were suppressed in the endothelium of the aorta in db/db mice as well as in human umbilical vein endothelial cells, which were treated with high glucose (HG). Increased expression of miR-383 decreased expression of SIRT1, while suppression of miR-383 promoted expression of SIRT1 in human umbilical vein endothelial cells (HUVECs). Furthermore, suppression of miR-383 following transfection with miR-383 suppressor repressed cell death and generation of ROS in HUVECs. SIRT1 knockdown by siRNA-SIRT1 reversed the suppressive effect of miR-383 inhibition on ROS production and cell apoptosis induced by HG treatment. Overall, the findings of our research suggested that suppression of miR-383 repressed oxidative stress and reinforced the activity of endothelial cells by upregulation of SIRT1 in db/db mice, and targeting miR-383 might be promising for effective treatment of diabetes.